5σ tension between Planck cosmic microwave background and eBOSS Lyman-alpha forest and constraints on physics beyond ΛCDM - Keir K. Rogers; Vivian Poulin (Physical Review Research)
We find that combined Planck cosmic microwave background, baryon acoustic oscillations, and supernovae data analyzed under Λ cold dark matter (ΛCDM) are in 4.9σ tension with the extended Baryon Oscillation Spectroscopic Survey (eBOSS) Lyα forest in inference of the linear matter power spectrum at wave number ∼1hMpc^{−1} and redshift = 3. Model extensions can alleviate this tension: running in the tilt of the primordial power spectrum (α_{s}∼−0.01); a fraction ∼(1−5)% of ultralight axion dark matter (DM) with particle mass ∼10^{−25} eV or warm DM with mass ∼10 eV. The new Dark Energy Spectroscopic Instrument survey, coupled with high-accuracy modeling, will help distinguish the source of this discrepancy.